(untitled) (Journal of Building and Road Research, 2022)
This paper reviews the main findings and conclusions drawn from research studies that dealt with the application of the CPT method for estimating important geotechnical characteristics of Sudanese soils. Great efforts were made in previous research works to develop correlation relationships between CPT data and soil parameters determined from laboratory testing of samples obtained from different states in the country. Generally, the CPT has proved to be useful in the characterization of studied soil behavior. Sound relationships have been proposed for predicting the SPT, undrained shear strength, compressibility, over-consolidation ratio and swelling potential of local soils from CPT data. It has been shown that the relationships between CPT and the soil parameters considered are affected by some factors such as the type, moisture condition and stress history. The relationships based on CPT proposed for the SPT and undrained soil strength have been revised and modified using further databases and more rational analysis techniques made available in recent times. The developed correlation relationships are useful for evaluation of important soil parameters that are needed for the design and construction of foundations in future engineering projects.